Pengaruh Pemahaman Kitab Fathul Qorib Terhadap Kualitas Shalat Santri Di Pondok Pesantren Hidayatul Qur’an, Batanghari Lampung Timur - Irawan, Dedi; Nauvaldy, M. Khanifa Rizki; Bima Fandi A (DIMAR: Jurnal Pendidikan Islam, 2023)
Prayer is an obligation for every Muslim; even in an illness, one must perform the five daily prayers under any circumstances and anywhere. Prayer is a worship and a compulsory act for a Muslim. Because that is one of the important pillars of Islam, which is second only to shahada. The purpose of the research to be achieved in this study is to determine the influence of understanding the Book of Fathul Qorib on the quality of student prayers at the Hidayatul Qur’an Islamic Boarding School in Batanghari, Lampung Timur. This type of research uses a “causal associative” with a quantitative approach for data collection techniques using observation, questionnaires, tests and documentation.  Based on the study's results, the author can conclude that understanding the book of Fathul Qarib influences the quality of student prayer worship at the Hidayatul Qur'an Islamic Boarding School in Batanghari, East Lampung. The value of t calculated > ttable is 2.562> 2.0 24, and the significance value is 0.0 14 < 0.05, The magnitude of the coefficient of determination (R Square) is 0.147 or equal to 14.7%. This number means that the variable of Understanding the Book of Fathul Qarib (X) affects the variable Quality of Santri Prayer (Y) by 14.7%. At the same time, the rest (100% - 14.7% = 85.3%) are influenced by other variables outside this regression equation or not studied.